Dynamic contrast-enhanced magnetic resonance imaging: fundamentals and application to the evaluation of the peripheral perfusion - Gordon, Yaron; Partovi, Sasan; Müller-Eschner, Matthias; Amarteifio, Erick; Bäuerle, Tobias; Weber, Marc-André; Kauczor, Hans-Ulrich; Rengier, Fabian (Cardiovascular Diagnosis and Therapy, 2014)
Introduction: The ability to ascertain information pertaining to peripheral perfusion through the analysis of tissues’ temporal reaction to the inflow of contrast agent (CA) was first recognized in the early 1990’s. Similar to other functional magnetic resonance imaging (MRI) techniques such as arterial spin labeling (ASL) and blood oxygen level-dependent (BOLD) MRI, dynamic contrast-enhanced MRI (DCE-MRI) was at first restricted to studies of the brain. Over the last two decades the spectrum of ailments, which have been studied with DCE-MRI, has been extensively broadened and has come to include pathologies of the heart notably infarction, stroke and further cerebral afflictions, a wide range of neoplasms with an emphasis on antiangiogenic treatment and early detection, as well as investigations of the peripheral vascular and musculoskeletal systems. - Applications to peripheral perfusion: DCE-MRI possesses an unparalleled capacity to quantitatively measure not only perfusion but also other diverse microvascular parameters such as vessel permeability and fluid volume fractions. More over the method is capable of not only assessing blood flowing through an organ, but in contrast to other noninvasive methods, the actual tissue perfusion. These unique features have recently found growing application in the study of the peripheral vascular system and most notably in the diagnosis and treatment of peripheral arterial occlusive disease (PAOD). - Review outline: The first part of this review will elucidate the fundamentals of data acquisition and interpretation of DCE-MRI, two areas that often remain baffling to the clinical and investigating physician because of their complexity. The second part will discuss developments and exciting perspectives of DCE-MRI regarding the assessment of perfusion in the extremities. Emerging clinical applications of DCE-MRI will be reviewed with a special focus on investigation of physiology and pathophysiology of the microvascular and vascular systems of the extremities.
Gesehen am 18.02.2021